Fast-Food Consumer Purchasing Decisions: Quality, Price, and Service Impact: Pengaruh Kualitas Produk, Harga, dan Kualitas Layanan terhadap Keputusan Pembelian Konsumen: Studi Kasus Restoran Cepat Saji - Vebia Afni Riszaini; Lilik Indayani (Academia Open, 2023)
This quantitative study investigates the influence of product quality, price, and service quality on purchasing decisions at a fast-food restaurant, utilizing a purposive sampling technique to gather data from 170 participants. Questionnaires were distributed using a modified 4-point Likert scale. The collected data underwent data quality testing, classic assumption testing, multiple linear regression analysis, and hypothesis testing. The findings reveal that product quality, price, and service quality each have a significant impact on purchasing decisions at the fast-food restaurant. Furthermore, the combined influence of these factors on purchasing decisions was also observed. This study highlights the importance of considering these factors to enhance consumer decision-making processes in the context of fast-food restaurants, thereby providing valuable insights for both practitioners and researchers in the field of consumer behavior. Highlights: Product quality, price, and service quality significantly influence consumer purchasing decisions at fast-food restaurants. This study utilizes quantitative research methods and a purposive sampling technique to examine the impact of these factors. The findings emphasize the importance of considering product quality, price, and service quality to enhance consumer decision-making processes in the fast-food industry. Keywords: consumer purchasing decisions, product quality, price, service quality, fast-food restaurant.